Crimes, criminals and cops. - Kulkarni, R.S. (New Delhi, 1990)
The book brings out not only the professional competence of the narrator in his investigation work but also the fact that his faimess as a police officer was appreciated even by his victims who had no rancour against him.
Keywords: Crimes